1999
DOI: 10.1046/j.1440-1746.1999.02033.x
|View full text |Cite
|
Sign up to set email alerts
|

C ASE R EPORT: Mucinous cholangiocarcinoma featuring a multicystic appearance and periportal collar in imaging

Abstract: A case of mucinous cholangiocarcinoma (CC), a rare histological type of CC, featuring unusual images is reported. The patient was hospitalized because of acute development of jaundice and fever. Computed tomography demonstrated multiple cystic lesions in the liver and a band-like low density area parallel to the intrahepatic portal vein, a so-called 'periportal collar'. Endoscopic cholangiography revealed a stricture of the hepatic duct with slight upstream dilatation. Cytology of the bile juice and fine-needl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Mucinous cholangiocarcinoma is the rarest type of cholangiocellular carcinoma,12, 20 and this carcinoma is reported to be derived from IPNB 15, 16, 21. IPNB is pathologically characterized by prominent intraductal papillary proliferation with delicate fibrovascular cores and frequent mucin hypersecretion,15, 16, 21 and it is regarded as the biliary counterpart of intraductal papillary mucinous neoplasm of the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Mucinous cholangiocarcinoma is the rarest type of cholangiocellular carcinoma,12, 20 and this carcinoma is reported to be derived from IPNB 15, 16, 21. IPNB is pathologically characterized by prominent intraductal papillary proliferation with delicate fibrovascular cores and frequent mucin hypersecretion,15, 16, 21 and it is regarded as the biliary counterpart of intraductal papillary mucinous neoplasm of the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…In the digestive tract, it is relatively common in the stomach and colon with poor prognosis, while infrequent in the pancreas with better prognosis than ductal adenocarcinoma (5). It is very rarely seen in the biliary tract with a 0.8% reported incidence in autopsied cholangiocarcinoma cases as described in ‘mucinous intrahepatic cholangiocarcinoma’ by Nakajima et al in 1988 (4). The clinical and imaging features of colloid carcinoma of the EHD have not yet been described due to rarity of this subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Hayashi et al described radiologic characteristics of two cases of mucinous type intrahepatic cholangiocellular carcinoma, including large mucinous lakes throughout the tumor without mucin excretion into the bile duct (3, 9). Mizukami et al (4) reported a unique presentation of mucinous carcinoma, most likely originating from the right hepatic duct. CT demonstrated multiple cystic lesions distributed adjacent to the portal area with a beaded appearance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations